Study of productivity and composition of four Syrian wild strains of oyster mushrooms on wheat straw and the effect of its growth in the substrate - أحمد, لونا (Latakia University Journal -Biological Sciences Series, 2024)
The research was carried out in 2021-2022 with the aim of studying the productivity and chemical composition of four wild strains of oyster mushroom P. ostreatus, and comparing them with a foreign cultivated strain (P.O) M453 as a control, and the effect of its growth on the chemical composition of the growing medium, in a randomized design the complete one. The studied strains (S19, S27, S38, and S41) were collected from different regions of the country, isolated and purified on PDA nutrient growth medium, then growing on wheat straw. After harvesting, productivity indicators were studied in terms of fruit body weight, number and weight of fruit clusters, productivity and biological efficiency. The chemical content of the fruit bodies was studied. The substrate was analyzed before and after cultivation. The results indicated clear differences between the strains in indicators of fruiting bodies growth and productivity, as the average number of fruiting bodies per cluster ranged between 10.75 and 21.25 fruiting bodies, the average number of clusters ranged between 3.75 and 4 clusters, and the average weight of the fruiting cluster ranged between 343. 38 and 495.75g, and the average productivity ranged between 239.94-324.63 g/kg, and the biological efficiency varied between 84 and 109.96%. The study of the chemical content of the studied strains showed that there were large significant differences in the strains’ content of nutritional elements. The protein content of all strains (19.29-29.77%) was good. The result showed that all strains are good in terms of the most important production and quality traits and can be adopted and used in the commercial production of oyster mushrooms. The results also showed a decrease in the C/N ratio in the substrate after cultivation of oyster mushroom strains, a decrease in the substrate’s content of dry matter and fiber, and an increase in its content of ash, total carbohydrates, and protein.